P07.14 Aptima tv naat test performance in gum clinics and primary care in the uk. (13th September 2015) - Nicholls, J; Muir, P; North, P; Ferguson, R; May, M; Turner, K; Macleod, J; Horner, P
Abstract : Introduction: The Aptima TV NAAT for the detection of Trichomonas vaginalis (TV) is ~ 100% sensitive compared to wet mount microscopy (50%) or culture (75%). Asymptomatic women attending genitourinary medicine (GUM) clinics and patients in primary care are often not tested for TV, as the prevalence and sensitivity of current tests is assumed to be too low for testing to be cost effective. Our aim was to determine how many additional cases were identified with the new test and whether self-taken and clinician-taken vaginal swabs are of equivalent sensitivity in symptomatic GUM patients. Methods: Patients were tested using the Aptima TV NAAT alongside existing testing methods. Results: The positivity of TV determined by TV NAAT was 4.8% (26/543) and 1.8% (28/1593) in women with and without symptoms attending GUM and 2.7% (95/3512) and 1.1% (41/3593) respectively in primary care. TV NAAT significantly outperformed our existing testing methods. In a subset of 491 GUM patients in whom all tests were performed, 14/23 (61%) TV NAAT positive patients were identified on wet prep or culture (p = 0.004). In a subset of 2930 primary care patients in whom all tests were performed, 19/74 (26%) TV NAAT positive patients were identified on wet prep or culture (p < 0.0001). These results may reflect deterioration of specimens in transport to the laboratory. Self- taken vaginal swabs were equivalent in sensitivity to clinician taken swabs; of the 26 patients who tested positive on either NAAT test, 25 tested positive on self-taken swab and 21 tested positive on clinician taken swab (p = 0.51). Conclusion: Testing women attending GUM clinics and in primary care with the Aptima TV NAAT test will identify additional cases and should replace conventional microbiological testing methods if found to be cost-effective. Disclosure of interest statement: Hologic provided the tests for the Aptima TV NAAT research study and have sponsored the authors to present this data at ISSTDR.